Determine the Best Location for Maintenance Centers and Breakdown Management for Drinking water Supply Network for the City of Jableh using GIS - سلمان فاطمه (Latakia University Journal -Engineering Sciences Series, 2024)
The crisis has left Syria with numerous impacts, left its impact on all the Syrian governorates, and its results have been reflected on the economic and service realities of the population. The water sector is considered one of the sectors affected by the effects of this crisis, from cutting water to damaging water networks, and the suspension of many major pumping stations and wells. This research aims to identify how to manage and maintain the drinking water network in cities by using geographic information systems technology GIS in order to assist decision makers in reaching less costly and timely solutions, especially in the circumstances of the crisis that Syria suffers in general, through collecting, entering, treating and managing the rules Spatial and descriptive data for the drinking water network in the city of Jableh as a case study with a focus on the system for managing and maintaining this network based on the spatial analysis of the faults of this network over three years (2017-2018-2019) and choosing the ideal place for maintenance centers in this city.